Thermal property and microstructure of Al nanopowders produced by two evaporation routes - 陈亮 宋武林 郭连贵 谢长生 (Transactions of Nonferrous Metals Society of China, 2009)
Al nanopowders with diameters ranging from 20 to 50 nm passivated by Al2O3 coatings were produced by two different evaporation routes： induction heating evaporation （IHE） and laser-induction complex heating evaporation （LCHE）. Thermal property of the nanopowders was investigated by differential thermal analysis （DTA） in dry oxygen environment. The results show that Al nanopowders produced by LCHE have the oxidation enthalpy change （AH） of 3.54 kJ/g, while the AH of A1 produced by IHE is 1.18 kJ/g. The phase constitution and microstructures of these nanopowders were revealed using X-ray diffraction （XRD） analysis, transmission electronic microscopy （TEM） and high-resolution transmission electronic microscopy （HRTEM）. The results show that the two powders have the same composition and mean particle size, as well as the thickness of Al2O3 coatings （3-5 nm）. Defects were observed on the surfaces of the particles by LCHE. However, the defects were not detected by HRTEM on the surfaces of the particles by IHE. The results prove that there exists excessive stored energy in Al nanopowders by LCHE because of the nonequilibrium condition brought by laser and the defects are the storage area of the excessive stored energy. Propellants composed ofAl nanopowders by LCHE show higher energy level and specific impulse.